The Spo7 sequence LLI is required for Nem1-Spo7/Pah1 phosphatase cascade function in yeast lipid metabolism - Mirheydari, Mona (J Biol Chem, 2020)
The Nem1-Spo7 complex in the yeast Saccharomyces cerevisiae is a protein phosphatase that catalyzes the dephosphory-lation of Pah1 phosphatidate phosphatase, required for its translocation to the nuclear/endoplasmic reticulum membrane. The Nem1–Spo7/Pah1 phosphatase cascade plays a major role in triacylglycerol synthesis and in the regulation of phospholipid synthesis. In this work, we examined Spo7, a regulatory subunit required for Nem1 catalytic function, to identify residues that govern formation of the Nem1-Spo7 complex. By deletion analysis of Spo7, we identified a hydrophobic Leu-Leu-Ile (LLI) sequence comprising residues 54–56 as being required for the protein to complement the temperature-sensitive phenotype of an spo7Δ mutant strain. Mutational analysis of the LLI sequence with alanine and arginine substitutions showed that its overall hydrophobicity is crucial for the formation of the Nem1-Spo7 complex as well as for the Nem1 catalytic function on its substrate, Pah1, in vivo. Consistent with the role of the Nem1–Spo7 complex in activating the function of Pah1, we found that the mutational effects of the Spo7 LLI sequence were on the Nem1–Spo7/Pah1 axis that controls lipid synthesis and related cellular processes (e.g. triacylglycerol/phospholipid synthesis, lipid droplet formation, nuclear/endoplasmic reticulum membrane morphology, vacuole fusion, and growth on glycerol medium). These findings advance the understanding of Nem1-Spo7 complex formation and its role in the phosphatase cascade that regulates the function of Pah1 phosphatidate phosphatase.